![tg3\alpha=tg(2\alpha+\alpha)=\frac{tg2\alpha+tg\alpha}{1-tg2\alpha*tg\alpha}=\frac{\frac{2tg\alpha}{1-tg^{2}\alpha}+tg\alpha}{1-\frac{2tg\alpha }{1-tg^{2}\alpha}*tg\alpha}=\frac{2tg\alpha+tg\alpha(1-tg^{2}\alpha)}{1-tg^{2}\alpha-2tg^{2}\alpha}=\frac{3tg\alpha-tg^{3}\alpha}{1-3tg^{2}\alpha} tg3\alpha=tg(2\alpha+\alpha)=\frac{tg2\alpha+tg\alpha}{1-tg2\alpha*tg\alpha}=\frac{\frac{2tg\alpha}{1-tg^{2}\alpha}+tg\alpha}{1-\frac{2tg\alpha }{1-tg^{2}\alpha}*tg\alpha}=\frac{2tg\alpha+tg\alpha(1-tg^{2}\alpha)}{1-tg^{2}\alpha-2tg^{2}\alpha}=\frac{3tg\alpha-tg^{3}\alpha}{1-3tg^{2}\alpha}](https://tex.z-dn.net/?f=tg3%5Calpha%3Dtg%282%5Calpha%2B%5Calpha%29%3D%5Cfrac%7Btg2%5Calpha%2Btg%5Calpha%7D%7B1-tg2%5Calpha%2Atg%5Calpha%7D%3D%5Cfrac%7B%5Cfrac%7B2tg%5Calpha%7D%7B1-tg%5E%7B2%7D%5Calpha%7D%2Btg%5Calpha%7D%7B1-%5Cfrac%7B2tg%5Calpha%20%7D%7B1-tg%5E%7B2%7D%5Calpha%7D%2Atg%5Calpha%7D%3D%5Cfrac%7B2tg%5Calpha%2Btg%5Calpha%281-tg%5E%7B2%7D%5Calpha%29%7D%7B1-tg%5E%7B2%7D%5Calpha-2tg%5E%7B2%7D%5Calpha%7D%3D%5Cfrac%7B3tg%5Calpha-tg%5E%7B3%7D%5Calpha%7D%7B1-3tg%5E%7B2%7D%5Calpha%7D)
Sin5α = Sin(3α + 2α) = Sin3αCos2α + Sin2αCos3α = (3Sinα - 4Sin³α)(1 - Sin²α) + (4Cos³α - 3Cosα)*2SinαCosα = 3Sinα - 6Sin³α -4Sin³α + 8Sin⁵α + 2SinαCos²α(4Cos²α - 3) = 3Sinα - 10Sin³α + 8Sin⁵α +2Sinα(1 - Sin²α)(4 - 4Sin²α - 3 = 3Sinα - 10Sin³α + 8Sin⁵α + (2Sinα - 2Sin³α)(1 - 4Sin²α) = 3Sinα - 10Sin³α + 8Sin1⁵α +2Sinα - 8Sin³α - 2Sin³α + 8Sin⁵α = 5Sinα - 20Sin³α + 16Sin⁵α